Inflammatory Pathways to Carcinogenesis: Deciphering the Rheumatoid Arthritis–Lung Cancer Connection - Abou Hjeily, Boushra; Nevaneeth, Briana Candace; Samborski, Włodzimierz; Szekanecz, Zoltán; Grygiel-Górniak, Bogna (Cancers, 2025)
Rheumatoid arthritis (RA) is the most common chronic autoimmune arthropathy. If the disease is aggressive or left untreated, it becomes debilitating, affects a patient’s functionality, and reduces the quality of life. Disease-modifying anti-rheumatic drugs (DMARDs), both conventional, targeted, and biological, decrease the disease progression and are key components of effective treatment. Recently, there has been a continuous debate about the possible carcinogenicity of various DMARDs. Lung cancer is a leading cause of cancer death worldwide. The available data show an increased risk of lung cancer in RA patients, but the link between RA and cancer is poorly understood. Carcinogenesis in RA seems to be related to chronic inflammation, familial predisposition, risky behaviors (e.g., smoking), and iatrogenic complications. The main mechanisms of carcinogenic processes in patients with RA are the up-regulation of interleukin-6 (IL-6) cytokine production and wingless/integrated WNT signaling. Up-regulation of WNT5A is an important mechanism that links chronic inflammatory pathways to carcinogenesis observed in RA patients. Concomitant up-regulation of transcription factor STAT3 promotes cell proliferation and inhibits apoptosis. Conversely, suppressed inflammatory processes by DMARDs may decrease the risk of lung cancer. In this article, we discuss the molecular mechanisms of lung cancer in RA and the role of DMARDs in this process. Furthermore, we analyze the molecular effect of drug-induced cancer, which affects transcription factors and thus modulates carcinogenic processes. Finally, we describe risk factors and present preventive and therapeutic approaches.